Harvesting keratolimbal allografts from corneoscleral buttons: a novel application of cyanoacrylate adhesive. Issue 11 (24th October 2008) - Lim, L T; Bhatt, P R; Ramaesh, K
Abstract : Aim: To describe an alternative and novel technique using cyanoacrylate glue to achieve successful limbal tissue dissection, from an organ culture media stored corneoscleral button, without an artificial anterior chamber. Methods: A donor corneoscleral button (leftover from penetrating keratoplasty) was divided into two equal semicircular halves. A thick layer of tissue adhesive (N-butyl-2-cyanoacrylate) was spread on a sterile rubber block (the under surface of the donor punch). One half of the donor corneoscleral rim was placed epithelial side up on the adhesive and allowed to attach firmly to the block. This composite provided stability to the donor rim allowing lamellar dissection of the limbal tissue to be performed without damaging the limbal epithelium. Results: Regular, partial-thickness limbal tissue was obtained. There was no histological evidence of glue or cellular toxicity of the harvested limbal stem cells. This harvested tissue had been grafted successfully in patients with limbal stem cell deficiency also undergoing keratoplasty. Conclusions: Tissue adhesive can be a simple, effective and useful tool in the dissection and harvesting of corneal limbal stem cell allografts from corneoscleral buttons stored in organ culture media.